Motivation Of Pregnant Women Regarding Breast Care At Tpmb Gayaman Village, Mojoanyar District, Mojokerto District - Mail, Erfiani; Farida Yuliani; Fitria Edni Wari (Universitas STRADA Indonesia, 2025)
Taking care of your breasts both during pregnancy and after giving birth will maintain the shape of your breasts and also facilitate the flow of breast milk. (Manuaba, 2010). The impact that arises if breast care is not carried out and breast care is only carried out after delivery, then the mother will experience problems such as breast milk not coming out, nipples not protruding, little milk production, breast infections, mastitis, and sore nipples. In this study, the aim was to determine the motivation of pregnant women regarding breast care at TPMB, Gayaman Village, Mojoanyar District, Mojokerto Regency. This research was conducted in this type of research is descriptive. The design in this research is survey The variables used in this research are Motivation of Pregnant Women Regarding Breast Care in TPMB Gayaman Village, Mojoanyar District, Mojokerto Regency.